The importance of the implementation of the pharmacy and therapeutic commission in a regional hospital in the alto-sertão paraibano (Research, Society and Development, 2022)
The Pharmacy and Therapeutics Commission (CFT) is a collegiate instance of a consultative nature, composed of a multidisciplinary and deliberative team, important for health education and hospital management. This study aims to report the experience lived at Hospital Regional de Catolé do Rocha (HRCR) and show the importance of implementing a CFT in the hospital. This is an experience report during the residency in collective health at the Regional Hospital Américo Maia de Vasconcelos, in Catolé do Rocha, following the method proposed by Jara-Holliday. The HRCR, receives patients referred by the municipalities of the eighth health region, because it is a service of greater complexity and degree of technological density, it was designed to offer secondary care services. However, due to the lack of well-defined clinical protocols and the absence of a CFT, the hospital performs low-complexity care, negatively contributing to hospital costs and expenses, as well as influencing the service time of users. It is concluded that if implemented, the Pharmacy and Therapeutics Commission can be effective in the management process of the HRCR, with the elaboration of therapeutic protocols and standardization of medicines, thus seeking the safety and rationality of the use of medicines, greater protagonism of the Pharmacist and generation of savings (cost-effectiveness). In addition to favoring the quality of service provided to users, culminating in a better quality of life for patients and reduced length of stay. The effective insertion of CFT is a positive health action for management and users.